2019
DOI: 10.1016/j.htct.2018.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency, still a rarity in children with sickle cell anemia in Ile-Ife, Nigeria

Abstract: In this study, children with sickle cell anemia were evaluated for iron deficiency. Serum ferritin and free erythrocyte protoporphyrin free erythrocyte protoporphyrin (FEP) levels, mean corpuscular volume mean corpuscular volume (MCV) and mean corpuscular hemoglobin mean corpuscular hemoglobin (MCH) were used in determining their iron status. The study was done at Pediatric Hematology Outpatient Clinic of the Obafemi Awolowo University Teaching Hospitals’ Complex, Ile-Ife. Forty-eight HbSS subjects in steady s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…The mean MCV, MCH and MCHC, which are the markers of iron status, were all within normal ranges [ 20 ]. This finding is similar to other reports [ 7 , 21 , 22 ]. The normal iron markers in children with SCA may be attributed to increased red cell turnover and repeated blood transfusion.…”
Section: Discussionsupporting
confidence: 93%
“…The mean MCV, MCH and MCHC, which are the markers of iron status, were all within normal ranges [ 20 ]. This finding is similar to other reports [ 7 , 21 , 22 ]. The normal iron markers in children with SCA may be attributed to increased red cell turnover and repeated blood transfusion.…”
Section: Discussionsupporting
confidence: 93%
“…However, it should be mentioned that the majority of enrolled patients had normal MCV and MCH values. This observation is indeed supported by the observation of previous authors who found that most of patients with sickle cell disease had normal MCV, MCH and even MCHC values [19,21,22]. These indices reflect normal iron status, which is the result of increased red cell turn-over and blood transfusion in patients with sickle cell disease.…”
Section: Discussionsupporting
confidence: 85%
“…Sickle cell children in this study despite the anaemia had a normal Ferritin level, going on the same line with the findings of Odunlade et al in Nigeria [17] concluding that despite the anaemic status of sickle cell patients, their Ferritin level is usually normal or high.…”
Section: Anaemia Inflammation and Leucocytosissupporting
confidence: 91%